Morphology, biology and phylogeny of Xenos gadagkari sp.nov. (Strepsiptera: Xenidae): an endoparasite of Polistes wattii (Hymenoptera: Vespidae) - Nain, Deepak; Rana, Anjali; Raychoudhury, Rhitoban; Sen, Ruchira (Zootaxa, 2024)
We report the morphology, biology and phylogeny of a new strepsipteran endoparasitic species: Xenos gadagkari, which stylopises the primitively eusocial wasp Polistes wattii from Punjab, India. We report a high abundance of the endoparasite in P. wattii population of our study area and provide the morphological description of adult males, male puparium and neotenic females. This species is sufficiently different from other species of Xenos reported from social wasps and therefore, constitutes a new species, X. gadagkari Sen and Nain, sp. nov. Although there are a few reports of strepsipteran parasitoids from India, this is the first confirmed report with a description of a Xenos species from the Indian population of P. wattii. Our findings contribute to the growing body of knowledge on Xenos and provide a foundation for future behavioural, microbial and molecular studies on this enigmatic group of insects.